Daydreams and the True Self: Daydreaming Styles Are Related to Authenticity. (December 2016) - Williams, Honey; Vess, Matthew
The feeling of knowing and expressing one's true self (i.e., authenticity) is a critical component of well-being. This research examined how patterns of inner mental experience, or daydreaming styles, relate to differences in authenticity. In two online studies, participants completed a series of personality measures, including measures of daydreaming styles and authenticity. Study 1 ( N = 201) and Study 2 ( N = 203) generally supported our hypotheses. Positive constructive daydreaming predicted greater feelings of authentic living and lower feelings of true self-alienation, and guilty/fear-of-failure daydreaming predicted lower levels of authentic living and greater feelings of both true self-alienation and acceptance of external influence. Moreover, we found that poor attentional control was a consistent positive predictor of true self-alienation and a weak predictor of acceptance of external influence. These findings offer novel insight into how daydreaming relates to people's subjective sense of knowing and being who they truly are.